Law Enforcement and Managerial Criminal Responsibility in Corruption of People's Business Credit Distribution at BRI Bone Pantai Unit - Yahya Boudelo; Dian Ekawaty Ismail; Erman I. Rahim (International Journal of Law, Crime and Justice, 2025)
This study discusses law enforcement against corruption crimes that occur in the process of providing People's Business Credit (KUR) facilities at the BRI Bone Pantai Unit as well as the form of criminal responsibility from the management of the banks involved. Through a normative-empirical approach, this study illustrates the weak internal supervision system of banks and the inefficiency of coordination between law enforcement that causes state losses of billions of rupiah. The findings show that the modus operandi in the form of data engineering and abuse of authority is carried out by bank employees in collaboration with external parties. The law enforcement carried out has not touched the structural roots of the weaknesses of the banking system and business ethics in the distribution of KUR. In the context of Lawrence M. Friedman's theory of legal systems, aspects of the structure, substance, and culture of the law show a failure to guarantee accountability and prevention. Therefore, the reconstruction of law enforcement needs to involve systemic improvements, the strengthening of management's criminal responsibility, and the strengthening of the capacity of the bank's internal supervisory institutions so that public trust in the KUR program can be restored.